A systematic review and meta-analysis comparing tumor progression and complications between radiofrequency ablation and thyroidectomy for papillary thyroid carcinoma - Sun, Yuan-dong; Zhang, Hao; Zhu, Hai-tao; Wu, Chun-xue; Chen, Miao-ling; Han, Jian-jun (Frontiers in Oncology, 2022)
Background: Papillary thyroid cancer (PTC) is the most frequent thyroid cancers worldwide. The efficacy and acceptability of radiofrequency ablation (RFA) in the treatment of PTC has been intensively studied. The aim of this study is to focus on extra detailed that may influent for PTC or papillary thyroid microcarcinoma (PTMC). Materials and Methods: We identified a total of 1987 records of a primary literature searched in PubMed, Embase, Cochrane library and Google Scholar by key words, from 2000 to 2022. The outcome of studies included complication, costs, local tumor progression. After scrutiny screening and full-text assessment, 6 studies were included in the systematic review. Heterogeneity was estimated using I2, and the quality of evidence was assessed for each outcome using the GRADE guidelines. Results: Our review enroled 1708 patients reported in 6 articles in the final analysis. There were 397 males and 1311 females in the analysis. Two of these studies involved PTC and four focused on PTMC. There were 859 patients in the RFA group and 849 patients in the thyroidectomy group. By contrast, the tumor progression of RFA group was as same as that surgical groups (odds ratio, 1.31; 95% CI, 0.52-3.29; heterogeneity [I2 statistic], 0%, p=0.85). The risk of complication rates was significantly lower in RFA group than in surgical (odds ratio, 0.18; 95% CI, 0.09-0.35; heterogeneity [I2 statistic], 40%, p=0.14). Conclusions: RFA is a safe procedure with a certain outcome for PTC. RFA can achieve a good efficacy and have a lower risk of major complications.